2015
DOI: 10.1002/jnr.23553
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in neurotrophic factors and neurite outgrowth in the major pelvic ganglion following cavernous nerve injury

Abstract: Despite nerve-sparing radical prostatectomy, nerve damage and erectile dysfunction (ED) prevails and preventing neurodegeneration is of great importance. Neurotrophic factors and neurite outgrowth were characterized in major pelvic ganglia (MPG) following bilateral cavernous nerve injury (BCNI). Young male Sprague-Dawley rats underwent sham or BCNI surgery and intracavernosal pressure to mean arterial pressure ratio (ICP/MAP) was measured 2, 7, 14, 21, 30 and 60 days following injury (n=8/group). MPG gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…Our group has previously demonstrated an increase in gene expression of a variety of cytokines and chemokines in the MPG following BCNI [9,11,13]. In this study, we found that the gene expression of multiple pro-inflammatory cytokines and chemokines ( IL-1B, Il6, Tnfa, Tgfb, Ccl2, Ccr2) are up-regulated at 48 hours, 7 days, and 14 days after injury with maximal increase at 48 hours following BCNI.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Our group has previously demonstrated an increase in gene expression of a variety of cytokines and chemokines in the MPG following BCNI [9,11,13]. In this study, we found that the gene expression of multiple pro-inflammatory cytokines and chemokines ( IL-1B, Il6, Tnfa, Tgfb, Ccl2, Ccr2) are up-regulated at 48 hours, 7 days, and 14 days after injury with maximal increase at 48 hours following BCNI.…”
Section: Discussionsupporting
confidence: 56%
“…TaqMan Gene Expression Assays (Applied Biosystems, Carlsbad, CA, USA) were used to evaluate the gene expression of CD11b (Rn00709342_m1), CD68 (Rn01495634_m1), CCL2 (Rn00580555_m1), CD86 (Rn00571654_m1), inducible nitric oxide synthase (iNOS: Rn00561646_m1), IL-6 (Rn01410330_m1), IL-1β (Rn00580432_m1), CD206 (Rn01487342_m1), IL-10 (Rn00563409_m1), and Arginase-1 (ARG1: Rn00691090_m1) and normalized to hypoxanthine guanine phosphoribosyl transferase (HPRT; Rn01527840_m1). All experiments were performed on 5 different whole MPGs from each group with triplicate technical replicate PCR reactions per sample [11]. M1/M2 index was used to evaluate the ratio of gene expression of M1 macrophage markers and M2 macrophage markers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All experiments were performed on 7 different whole paired MPGs from each group, with triplicate technical replicate PCR reactions per sample. 13 …”
Section: Methodsmentioning
confidence: 99%
“…MPGs were kept on ice in serum-free media (RPMI 1640 with 1% penicillin-streptomycin, GIBCO, Grand Island, NY) until they were embedded and cultured in reduced growth factor Matrigel (Corning, Tewksbury, MA) with vascular endothelial growth factor (VEGF; 25 μg/mL, R&D Systems, Minneapolis, MN) (n = 3 per group). 13 …”
Section: Methodsmentioning
confidence: 99%